The Effectiveness of Short Story Use On Students' Speaking Skill Development at SMPN 160 Jakarta - Ompusunggu, Retta Mestika (JET (Journal of English Teaching), 2018)
The use of short story as an essential component of second and foreign language teaching has recently been resurrected. Current studies also indicated that short story can facilitate effective learning of speaking. This study aimed at investigating whether short stories use was effective to develop students’ speaking in English as a foreign language (EFL) context. To achieve the aim, a pretest-posttest experiment design using two groups of experimental (n=30) and control (n=30) was conducted at SMPN 160 Jakarta. The control group was taught speaking using short stories, while the control group was taught speaking in the routine procedure of the English classes. The experiment occurred in six weeks, two forty-five-minutes-sessions per week. Data was collected using tests administering the interview technique. The results of the hypothesis test employing SPSS22.00demonstrated that short story use had a significant effect on the participants' speaking skills improvement. It was, therefore, recommended to use short story to help students develop their speaking performance. Keywords: EFL, short story, speaking skills